A Pope Coming from the East: John Paul II on the Situation of the Catholic Church in Romania (1978-1989) - BUCUR, Ioan-Marius (Studia Universitatis Babeș-Bolyai Historia, 2025)
As was the case with the entire East-Central European region, the instatement of Communism in Romania brought an unprecedented wave of persecution, coercion, censorship of various religious denominations, with the Greek-Catholic and Roman Catholic churches counting themselves among the main victims of the abusive force unleashed by the newly installed regime. Weathering the storm of the brutal repression that characterized the early Communist years, the resilient religious minorities would find ways to resist the harsh persecutions directed against them, while at the same time attempting to take advantage of the limited opportunities brought by the internal evolution of the regime, as well as by the international developments of their time. On the background of a consistently strenuous relation between political authorities and minority religious communities, the election of John Paul II as Pope became an influential moment for the course of both Catholic rites in Romania, as they followed their way through the meandering final years of Romanian Communism. Rezumat: Instituționalizarea regimului comunist în Europa Central-Răsăriteană a generat, între altele, un val sistematic de persecuții, coerciție și cenzură împotriva diferitelor denominații religioase, bisericile Greco-Catolică și Romano-Catolică numărându-se printre principalele victime ale terorii comuniste. Recursul la coerciție și unele concesii, mai cu seamă începând cu anii 1960, a permis denominațiilor religioase să găsească anumite modalități de supraviețuire în confruntarea cu regimurile ideocratice. Dialogul angajat de Sfântul Scaun cu unele regimuri comuniste – în contextul destinderii internaționale - a avut rezultate contradictorii, România comunistă numărându-se între țările în care beneficiile dialogului pentru comunitățile catolice de ambele rituri au fost minore. Cuvinte-cheie: Comunism, represiune, Biserica Catolică, România, destindere internațională, minorități religioase, Sfântul Scaun, Ostpolitik, Papa Ioan Paul al-II-lea